The Effect of Integrated Nutrition Services on the Bodyweight of Underweight Children in Tanah Garam Health Center Coverage Area, Solok City, West Sumatera - Umar, Hermita Bus; Dianti, Nova; John Amos; Gusnedi; Zulferi (POLTEKKES KEMENKES PADANG, 2023)
Being underweight in children under five in Indonesia is still high. Integrated nutrition service is one of the innovative programs to overcome the underweight problem among under-five children. This study aims to determine the effect of integrated nutrition services on the bodyweight of underweight under-five children in Tanah Garam Health Center, Solok City. The study used a pre-experimental one-group pretest-posttest design. As the study subject, we recruited 30 healthy underweight children (WAZ -2<x<-3SD). Data collection includes body weight before and after the 10-days intervention. The body weight difference was analyzed using the dependent t-test. There was a significant change in children's weight as seen from the increase in the weight for age Z score (WAZ) after the provision of integrated nutrition service (P<0.05). About 76% of the subjects had bodyweight improvement. The mean body weight increase from baseline to end line was 0,25±1,17 kg, while the WAZ increased from -2.32 to -2.12 The implementation of integrated nutrition service could potentially improve the bodyweight of underweight children. It is recommended that all healthy underweight children participate in implementing the program.